Widely linewidth tunable lasers through cascaded four-wave mixing based phase modulation amplification. (17th March 2021) - Vikram, B S; Prakash, Roopa; Supradeepa, V R
Abstract: We demonstrate wide-range linewidth-tuning of a narrow-linewidth laser in the C-band up to 40 GHz through cascaded four-wave mixing (CFWM) based phase modulation amplification. Stimulated Brillouin scattering (SBS) severely limits the power scaling of narrow-linewidth lasers. Continuous tuning of the linewidth or temporal coherence of the laser to mitigate SBS is conventionally achieved through external phase modulation with white noise or other RF waveforms. However, the range of linewidth tuning is limited by the bandwidth and power of the electro-optic modulator. We overcome this through the use of FWM as a linewidth multiplier. To achieve linewidth multiplication, two tunable pumps line-broadened in electro-optic phase modulators with white noise are power scaled and propagated through highly nonlinear fiber. We achieve linewidth tuning up to ∼4 GHz using control of the noise waveform, while CFWM achieves a 10× multiplication of linewidth up to 40 GHz at a fixed wavelength. Linewidth tuning can be further scaled through power scaling or cascading multiple nonlinear stages. The proposed technique would be useful in nonlinearity control in narrow-linewidth laser amplifiers, high-resolution optical imaging, LIDAR, and infrared spectroscopy.